RHETORICAL MOVES IN TEN PAPUAN FOLKLORES: A CORPUS-BASED GENRE ANALYSIS - Jeanyfer Tanusy; Trisnowati Tanto (Universitas Padjadjaran, 2023)
ABSTRACT. This paper aims to examine the basic structure that builds the narrative of ten of the folklores in Papua using the genre approach within the field of English for Specific Purposes (ESP). The study focuses on the presence of the rhetorical moves in each of the story, which is hoped to show the stories’ main communicative purposes as well as their schematic structures. The study uses descriptive-qualitative approach, which analyses the data interpretatively by applying Swales’ (1990) genre theory, the Move-Structure theory and combining it with the narrative elements from Labov’s (1972) Narrative Structure theory. The findings indicate all ten stories share similar structures in general despite being written by different authors—each of them has the moves orientation, complications, resolution, and coda. However, in the move realization, each story has different steps and/or step cycles. These findings indicate that the ten stories share the same communicative purpose: giving information about how some things come to be, and that they belong to the same genre. It is hoped that this research adds to the literature of genre analysis in the perspective of linguistics as well as enriches the analysis of folk literature in Indonesia.